VALIDATION OF AN INSTRUMENT TO ASSESS THE KNOWLEDGE, ATTITUDE AND PRACTICE OF PUERPERAL WOMEN ABOUT THE GENERAL DANGER SIGNS OF THE NEWBORN - Soares , Maria Tereza Ferreira; Low , Sandra Trindade; Bastos , Maria Eduarda da Silva; Nascimento , Ana Júlia Falcão; Beserra , Maria Aparecida; Cantarutti , Lêda Maria de Lima; Neta, Maria Joana Pereira; Spinelli , Maria Benita Alves da Silva (Seven Editora, 2024)
The validation of an instrument is essential to ensure its reliability and accuracy. This study aimed to validate an instrument to assess the Knowledge, Attitude and Practice of puerperal women in rooming-in about general danger signs that the newborn may present. The study followed 7 stages: 1st conceptual structuring, 2nd definition of the instrument’s objectives, 3rd construction of the items and response scales, 4th selection and organization of the items, 5th structuring of the instrument, 6th content validation and 7th pre-test. Then, the psychometric properties of validity and reliability were evaluated. The statistical analysis of the data evaluated the CVI of pertinence, relevance and clarity for each item and all items evaluated in the final survey had CVI greater than or equal to 0.8 in the pertinence and relevance item. The final version of the instrument was validated containing 41 items separated by 3 domains, Knowledge, Attitude and Practices. The internal consistency of the instrument evaluated by Cronbach’s Coefficient showed that the instrument has high reliability with alpha equal to 0.88. Validating this instrument was fundamental, as it enabled the application, analysis, and adequate planning of interventions that can improve the care of newborns and reduce avoidable deaths. DOI:https://doi.org/10.56238/sevened2024.037-048